Minimal handle decomposition of smooth simply connected five-dimensional manifolds - Prishlyak, O. O. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
A theorem on the existence of the unique minimal topologic handle decomposition of differentiable simply connected five-dimensional manifolds is proved. For a decomposition of this sort, the number of handles of each index is given.